Company-provided further training in Germany and the Netherlands - Allaart, Piet [Verfasser]; Bellmann, Lutz [Verfasser]; Leber, Ute [Verfasser] (My University, 2009)
"This study investigates the impact of determining factors of firms' further training activities from a cross-country perspective. Since the differences in the institutional background of training are of special interest we choose the Netherlands and Germany. Using the IAB (German) and OSA (Dutch) establishment panels we are able to control for additional differences in country-specific labour market institutions, the personnel structure, the firm structure and technology. Holding everything else constant the firms' engagement in further training in the Netherlands is much higher than in Germany, especially in SME and with respect to older workers." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Betriebliche Weiterbildung; Weiterbildungsbeteiligung; Internationaler Vergleich; Vergleichende Berufsbildungsforschung; Bundesrepublik Deutschland; Niederlande